Understanding Collective Efficacy as a Racialized Process: Examining the Relationship Between Discrimination and Perceptions of Collective Efficacy - Chouhy, Cecilia (Race and social problems, 2023)
The current project examines whether perceptions of collective efficacy are racialized. Using a sample of Black and Latinx young adults in Chicago, we first investigate whether perceptions of discrimination vary across Chicago’s neighborhoods and whether neighborhood-level structural characteristics (concentrated disadvantage, immigrant concentration, residential stability) or neighborhood social processes (neighborhood-level collective efficacy) are related to their perceptions of discrimination. Our estimations show that perceptions of discrimination are endemic to Chicago’s neighborhoods and are not related with neighborhood-level structural characteristics. Second, we examine whether perceptions of discrimination predict perceiving less collective efficacy while controlling for neighborhood characteristics. Overall, individuals perceive less collective efficacy when they perceive being discriminated against. Third, we analyze the sources of perceptions of collective efficacy separately for Black and Latinx individuals. These results suggest that discrimination shapes Black individuals’ perceptions of their neighbors but do not hold for Latinx individuals. Supplemental analyses reveal that for Latinx individuals, discrimination undermines perceptions of collective efficacy only when is framed as related to their race. Taken together, our results suggest that racism is embedded in the way racialized individuals perceive their neighbors’ agreement regarding norms of intervention. In short, the results suggest that the formation of collective efficacy is racialized.